Education Islam as Foundation Formation Character Young generation - Arianto Arianto (Inspire Global Insight Journal, 2026)
Islamic education plays a crucial role in shaping the character of a young generation with noble morals and responsibility. Islamic values teach ethics, morality, and the discipline necessary to face challenges. life. Study This aim for analyze as far as where education Islam contribute towards the formation of character student. Method study Which used is approach quantitative with method A survey of 25 vocational school students showed that 85% of respondents felt that Islamic education helped them they understand importance mark moral in life daily. Besides That, 78% student States that material PIE Which given in school contribute to formation attitude discipline and not quite enough they answered. With thus, education Islam can become foundation main in form character generation young people who are qualified and have good morals.